Do more people in Europe need treatment for problems related to cocaine use? An analysis of cocaine treatment demand in 10 Western European countries - Jérôme Antoine; N. Berndt; B. Braun; D. Cairns; S. Jahr; A. Jones; W. Kuijpers; N. Llorens; S. Lyons; E. Maffli; N. Magliocchetti; L. Montanari; et al. (Lisbon Addictions 2019, 2019)
Background   Recent signals from different European monitoring sources have indicated increased cocaine production and availability. To investigate these signals, in 2018, EMCDDA conducted a targeted ‘trendspotter’ study to analyse information from different areas, including use and problems, market, and responses to cocaine related problems. This study suggested that the European drug market appears to be experiencing a surge in the availability of high-purity cocaine, with existing epidemiological data possibly suggesting increased use among specific groups.   The increase in the availability of high-purity cocaine coincides with the increase observed in recent years, in people in Europe seeking treatment for cocaine use. After a period of decline, between 2008 and 2014, the overall number of people in Europe entering treatment for the first time in their lives for powder cocaine misuse has increased by more than 20% (around 4000 clients) between 2014 and 2017. At a lower level, increases in the number of first time treatment entrants for crack cocaine were also reported by several countries.   Following a recent annual European meeting on drug treatment demand, a group of experts from nine countries (Belgium, France, Germany, The Republic of Ireland, Luxembourg, The Netherlands, Spain, Switzerland, United Kingdom) was set up with the objective of looking at trends in treatment demand data and of assessing what is happening to cocaine treatment demand in different European countries.   Objectives The aim of this current study is to analyse and understand trends in cocaine treatment demand in nine European countries and to provide insight into details on recent trends in the numbers, characteristics, and in the patterns of use of cocaine treatment demands in order to assist in understanding the increase observed since 2014.   Method To perform this analysis a common plan and a dataset appropriate for trend analysis will be used in each of the nine countries in order to avoid methodological bias in the results. A joinpoint regression analysis was applied to the pooled data for all countries and also separately to the data for each country.     Results Preliminary results from national datasets strongly suggest an increase in cocaine treatment demands in most of the nine participating countries. The analysis identified several subgroups with specific needs and which require targeted responses.